PEMBENTUKAN FUNGSI PENGARUH METEOROLOGI PADA PERSAMAAN GAUSS MENGGUNAKAAN SOFTWARE R - Rachmanu Eko Handriyono (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2017)
Air quality model is numerical tools to describe the air quality in an urban. One of the air quality models is gaussian model. Factors that influence the gaussian equation are the sources of pollution, meteorological factors, the kinetics of reactions in the atmosphere, and land forms. These studies formed the function of the influence of meteorology on gaussian equation of traffic activities in Ahmad Yani Street, Surabaya. Meteorological factors such as wind speed and direction, the distance from the source to the receptor, and the atmosphere stability is simulated using software applications R. The purpose of this study is to establish the code foundation of software R for meteorological factors. The results showed the influence of meteorological function model using R is able to produce the work easier and faster time. The influence of meteorological function form a formulation of dispersion coefficient Ïƒy dan Ïƒz requires variables such as pollution sources and receptor coordinates, wind direction and atmospheric stability class.